A contribuição de Celso Furtado sobre o ecodesenvolvimento / o Brasil na dependência e deterioração dos termos de troca à luz das cadeias globais de valor - Rodrigues, Felype Tadeu Neves (2023)
This article aims to analyze Celso Furtado's contribution to ecodevelopmentbased on a set of books published during the period of the economic miracle, between1968and 1973. In addition to the bibliographical analysis of the miracle, the secondaryobjectiveaims to reconcile the debate on the environment of the period with Celso Furtado's criticismof the Club of Rome in The Myth of Economic Development (1974). The set of worksanalyzed is faithful to a regional and heterogeneous perception of Brazil's ecodevelopment.This search for understanding ecodevelopment is present in all of the author's works intheperiod, highlighting his alignment with the international environmental framework. For this,in addition to the works published by Furtado in the miracle, it is necessary touseothersources of information such as an interview, the use of letters and his intermittent diary. Thearticle is structured in a systematic bibliographical review, started in Aproject for Brazil(1968); passing through Latin American economic formation (1969); later in Analysis oftheBrazilian model (1972); and finally in United States hegemony and LatinAmericanunderdevelopment (1973). In this way, the ecological debate between the United Nations, theClub of Rome and Celso Furtado is consolidated. These works present a constancyinthematuration of Furtado's thought in denouncing the consequences of deforestationthroughmonoculture based on satisfying consumption patterns, as well as showing howFurtado'sdiagnosis of the environment draws from the ecological context of the period andhowhe 8addresses, in its trajectory, alternatives for the dynamics of technical progress intheeconomics of renewable resources and Ecodevelopment